Disruption of FOXO3a-miRNA feedback inhibition of IGF2/IGF-1R/IRS1 signaling confers Herceptin resistance in HER2-positive breast cancer - Liyun Luo (Nature Portfolio, 2021)
Resistance to Herceptin represents a major challenge for successful treatment of HER2-positive breast cancer. Here, the authors demonstrate that the activation of the IGF2/IRS1 signal caused by disruption of a negative feedback loop between FOXO3a-miR-128/miR-30/miR-193 induces Herceptin resistance.